desenvolva as expressões abaixo
x^2-y^2÷3x^2×y^3
Soluções para a tarefa
Respondido por
3
Resposta:
=\frac{1}{3y^3}-\frac{1}{3x^2y}
Explicação passo-a-passo:
\mathrm{Aplicar\:as\:propriedades\:das\:frações}:\quad \frac{a\pm \:b}{c}=\frac{a}{c}\pm \frac{b}{c}
\frac{x^2-y^2}{3x^2y^3}=\frac{x^2}{3x^2y^3}-\frac{y^2}{3x^2y^3}
=\frac{x^2}{3x^2y^3}-\frac{y^2}{3x^2y^3}
=\frac{1}{3y^3}-\frac{y^2}{3x^2y^3}
=\frac{1}{3y^3}-\frac{1}{3x^2y}
Perguntas interessantes
História,
10 meses atrás
Matemática,
10 meses atrás
Física,
1 ano atrás
História,
1 ano atrás
Sociologia,
1 ano atrás